Revision of Cestocampa Condé (Diplura, Campodeidae), with description of a new species from caves in the eastern Iberian Peninsula - Sendra, Alberto; Arnedo, Miquel A.; Ribera, Carles; Teruel, S.; Bidegaray-Batista, L.; Conde†, B. (Zootaxa, 2012)
A new cave-dwelling Diplura, Cestocampa iberica, is described from the eastern Iberian Peninsula. The new species wascollected in ten caves located in the large karstic area occurring along the Castilian-Valencian branch of the IberianMountain Range. It closely resembles other Cestocampa spp., especially C. gasparoi and C. balcanica. The delimitationof Cestocampa is reviewed. Cestocampa balcanica is redescribed and C. kashiensis is removed from the genus andtransferred to Plusiocampa. A phylogeographic analysis, based on the cox1 mtDNA gene of the new species, reveals aclear geographic structure with high levels of population phylopatry, indicating limited dispersal capabilities as found inother soil arthropods. Evidence of gene flow between nearby localities suggests interconnections among nearby caves.Under certain climatic conditions the species may be able to disperse over the surface, as suggested by one presumed longdistance dispersal event.